EFL PRE-SERVICE TEACHERS' PERCEPTIONS OF TEACHING ASSISTANCE PROGRAM - Vetriana Aksam; Maulina Maulina; Syarif Amin (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to delve into EFL pre-service teachers' perceptions of teaching assistance provided through the teaching assistance Program. This study selected 8 pre-service teachers from Universitas Muhammadiyah Kendari purposively and used interview as the primary method of data collection. Through a description of thematic analysis, this study identified key themes related to EFL pre-service teachers' understanding of the teaching assistance program, the role of teaching assistance, and the benefits and challenges faced during the program. The findings demonstrated that EFL pre-service teachers comprehended the goals and advantages of the program, which included gaining practical experience in an elementary school context and improving their teaching abilities. But they also had to deal with a number of issues, such inadequate communication with the school staffs, lack of supporting teaching and learning facilities, and the used to be high standards set by both teachers and students. Benefits of instructional help, including improved interpersonal and professional abilities, were also discovered in this study. The current study proposes that pre-service teachers should be given extended time to prepare, endure more comprehensive instruction, and open more effective collaboration with teachers in the school in order to benefit from the adjustable teaching experiences. Consequently, this research contributes meaningful and valuable insights for enhancing the implementation of the teaching assistance program.